Use of Electrochemical Impedance Spectroscopy (EIE) for monitoring corrosion in concrete with tire residue and Metakaolin and investigation of its microstructure (Research, Society and Development, 2022)
This work monitors the corrosion of concrete with tire residue and metholim using the Electrochemical Impedance Spectroscopy (EIE) technique. One of the most frequent pathologies found in reinforced concrete is corrosion of reinforcements that involves risks to the safety of the structure. Among the various techniques to study and evaluate corrosion in this work was chosen the electrochemical impedance spectroscopy (EIE) that characterizes a wide variety of electrochemical systems. Specimens were molded in the trace of 1:2:1:0.60 being a reference (without adding residue), others with the addition of (5% in tire residue, in relation to the kid aggregate) and were also molded (5% and 15% in tire residue and 15% of metacaulim). The choice of the equivalent circuit was different depending on the amount of materials used, for the reference sample a series resistive circuit was used with a second parallel circuit composed of an R resistance and a CPE phase element. For mixtures with tire residue and metemolim, a further R/CPE parallel circuit was added. Micrographs obtained through scanning electron microscopy (SEM) and X-ray dispersive energy spectrometry (EDS) were also performed. The results showed that the sample with 5% tire residue and 15% metakaline residue: presented lower potential values when compared to the other two samples.  The analysis of the EDS paw all samples were observed as common elements of the cement matrix as: Mg, Al, Si, K, Ca and Fe.